MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DALAM MENGGAMBAR ILUSTRASI ALAM SEKITAR DENGAN MENGGUNAKAN MEDIA GAMBAR DI KELAS 6 SDN 16 ULAKAN TAPAKIS - AZWIR, Drs. Ariusmedi, M.Sn, Drs. Syafwan, M.Si (Serupa The Journal of Art Education, 2014)
This article aims to determine whether the use of media images can enhance the activity and learning outcomes of sixth grade students in learning about the natural illustration drawing subjects Culture Art and Skills (SBK) Ulakan Tapakis SDN 16 Padang Pariaman. This type of research is conducted action research (classroom action research) carried out in the 6th grade at SDN 16 Ulakan Tapakis, Padang Pariaman, which is located in the sub-district Rimbo Kerambil-Tapakis Ulakan Tapakis Padang Pariaman.The results showed that the use of Media Images can enhance the activity and student learning outcomes. Thus the use of media images can enhance the activity and student learning outcomes to draw illustrations of natural materials around.Keywords: Activity, learning outcomes and drawing illustrations about the nature of media images.